2019
DOI: 10.15760/nwjte.2019.14.1.6
|View full text |Cite
|
Sign up to set email alerts
|

Preparing Teacher Candidates to Collaborate with Families and Communities: Standards, Research, and Practice

Abstract: Preparing teacher candidates to engage with family and community in ways that align with the reality of today's classroom is a critically important aspect of fostering student academic success and well-being. This paper examines how a set of professional preparation standards, the teacher preparation literature, and a qualitative inquiry into the practices and challenges of kindergarten teachers working with family and community converge to inform the work of teacher educators. Implications of these three sour… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
5
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
4
1

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(5 citation statements)
references
References 23 publications
0
5
0
Order By: Relevance
“…However, evidence shows that during their professional preparation, most pre-service teachers have limited opportunities for interacting with parents (de Bruїne et al, 2014;Evans, 2013;Taylor & Kim, 2020). This can be achieved by providing experiences where pre-service teachers interact directly with parents so they can develop skills needed for establishing effective partnerships and to give meaning to knowledge gained in the classroom (Buchanan & Buchanan, 2019;de Bruїne et al, 2014;Mitsch et al, 2020). These interactions should take place within a prolonged period and should not be limited to only school but also to interacting at home and community.…”
Section: Engaging Parents In Schoolsmentioning
confidence: 99%
See 3 more Smart Citations
“…However, evidence shows that during their professional preparation, most pre-service teachers have limited opportunities for interacting with parents (de Bruїne et al, 2014;Evans, 2013;Taylor & Kim, 2020). This can be achieved by providing experiences where pre-service teachers interact directly with parents so they can develop skills needed for establishing effective partnerships and to give meaning to knowledge gained in the classroom (Buchanan & Buchanan, 2019;de Bruїne et al, 2014;Mitsch et al, 2020). These interactions should take place within a prolonged period and should not be limited to only school but also to interacting at home and community.…”
Section: Engaging Parents In Schoolsmentioning
confidence: 99%
“…Educators understand the critical role that parents play in their children's education (Mitsch, Branch, & Weglarz-Ward, 2020) and this calls for continued efforts to build strong home-school partnerships (Buchanan & Buchanan, 2019). Developing productive relationships with families is part of a teacher's professional role (de Bruїne et al, 2014), thus as teacher candidates embark on their professional journey, having knowledge on how to establish strong parent-teacher partnerships is critical.…”
Section: Introductionmentioning
confidence: 99%
See 2 more Smart Citations
“…Global research has shown that these competencies that encourage FIPE are frequently inconsistent in initial teacher education [14][15][16][17][18]. There is evidence that initial teacher education programmes pay little attention to preparing pre-service teachers to form these relationships [11,[19][20][21][22]. Particularly in Europe, research addressing how pre-service teachers are prepared to work with families is scarce [21,23,24], and there is even less focus on early childhood educators' master's degrees [19].…”
Section: Introductionmentioning
confidence: 99%